2021
DOI: 10.1016/j.ejro.2021.100372
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance versus computed tomography for the detection of retroperitoneal lymph node metastasis due to testicular cancer: A systematic literature review

Abstract: Introduction It is essential to see if MRI can be used as an alternative to CT for the detection of retroperitoneal lymphadenopathy in patients with testicular neoplasms. By doing so, the amount of radiation received by these young patients might be reduced. Material and methods A systematic literature review was carried out in 5 databases between January 1984 until December 2020. The articles included were randomized and non-randomized clinical trials, cross-sectional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…IR is widely used in areas such as medical nuclear energy and industrial manufacturing, and poses potential risks to human health. For example, acute doses can cause radiation burns and radiation sickness, while long-term low doses can lead to cancer ( 208 , 209 ). The testis, one of the most radiation-sensitive organs, can suffer significant damage from even low doses of radiation, such as sperm chromosome aberrations ( 210 ), motility decreased ( 211 ), swimming behavior impaired ( 212 ) and testis weights decreased ( 213 ).…”
Section: The Protective Effects Of Taurine Against Male Reproductive ...mentioning
confidence: 99%
“…IR is widely used in areas such as medical nuclear energy and industrial manufacturing, and poses potential risks to human health. For example, acute doses can cause radiation burns and radiation sickness, while long-term low doses can lead to cancer ( 208 , 209 ). The testis, one of the most radiation-sensitive organs, can suffer significant damage from even low doses of radiation, such as sperm chromosome aberrations ( 210 ), motility decreased ( 211 ), swimming behavior impaired ( 212 ) and testis weights decreased ( 213 ).…”
Section: The Protective Effects Of Taurine Against Male Reproductive ...mentioning
confidence: 99%
“…All the articles found through the search strategy were blindly uploaded to Mendeley; subsequently, the duplicates were removed using the Mendeley duplicate detection tool [16] . When the duplicates were removed, the screening process was performed based on title and abstract.…”
Section: Methodsmentioning
confidence: 99%
“…At present, CT remains the initial imaging modality for surveillance to assess retroperitoneal LNs [ 9 , 142 , 143 ]. Baessler et al carried out a research investigation [ 144 ] to assess the capability of CT radiomics in improving the prognostication of malignant histopathology in retroperitoneal lymph node metastases (LNM) from NSGCTs before post-chemotherapy retroperitoneal lymph node dissection (PC-RPLND).…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Some authors have suggested a more focused and concise MRI technique that specifically targets retroperitoneal lymph nodes, excluding inguinal and pelvic areas. This approach shortens the acquisition duration from roughly 30–35 min to just 12–13 min [ 9 , 11 ]. These recommendations align with guidance provided by ESMO and the Swedish and Norwegian Testicular Cancer Group (SWENOTECA), which endorse the utilization of contrast-enhanced CT scans for the initial staging and recommend employing retroperitoneal MRI for post-initial treatment follow-up to mitigate radiation exposure in individuals with TC [ 9 , 148 – 150 ].…”
Section: Future Perspectivesmentioning
confidence: 99%